2016
DOI: 10.1016/j.alcohol.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response

Abstract: Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is noteworthy, however, that compared to adults, adolescents have been described to be more reactive to stress and to stress-ethanol interactions. In a recent study we found significantly greater ethanol intake time in adolescent, but not in adult, rats given chronic restraint stress ( Fernandez et al, 2016 ).…”
Section: Discussionmentioning
confidence: 78%
“…It is noteworthy, however, that compared to adults, adolescents have been described to be more reactive to stress and to stress-ethanol interactions. In a recent study we found significantly greater ethanol intake time in adolescent, but not in adult, rats given chronic restraint stress ( Fernandez et al, 2016 ).…”
Section: Discussionmentioning
confidence: 78%
“…Intriguingly, 5 days of restraint-induced stress exacerbated free choice ethanol drinking in adolescent, but not adult rats. Furthermore, adult rats had a greater level of ethanol sedation in comparison adolescents rats, but only the adolescent animals exhibited ethanol-induced motor stimulation (Acevedo et al, 2013; Fernández et al, 2016), suggesting that stress modulates the effects of ethanol in an age-dependent manner. Interestingly, Pautassi’s group further reported that female rats that show high baseline anxiety levels displayed higher ethanol intake as compared to female rats with average levels of anxiety.…”
Section: Contributions From Latin Americamentioning
confidence: 99%
“…In a subsequent set of papers, Dr. Pautassi’s group compared the effects of acute or repeated restraint-induced stress during adolescence and adulthood on ethanol consumption in male and female rats (Acevedo et al, 2013, 2016; Fernández et al, 2016; Wille-Bille et al, 2017). The authors found no effects of acute restraint stress on spontaneous or ethanol-induced locomotion at either age, whereas adult rats showed an enhanced and long-lasting sedative effect due to ethanol exposure as compared to adolescent rats (Acevedo et al, 2013).…”
Section: Contributions From Latin Americamentioning
confidence: 99%
“…This technique allows collecting information about neurochemicals in the extracellular space by means of the implantation of a semipermeable probe (300-mm outer diameter). Indeed, after over 30 years, brain microdialysis still represents a very powerful approach whose pros and cons have been elegantly and thoroughly discussed in seminal reviews (Di Chiara, Tanda, & Carboni, 1996;Kennedy, 2013;Rocchitta & Serra, 2013). In particular, brain microdialysis has proven to be slightly invasive and characterized by a relatively low temporal resolution, and characterized by requiring an association with an analytical instrumentation for the analysis of collected samples (Rocchitta & Serra, 2013).…”
Section: Introductionmentioning
confidence: 99%